Heterojunction of Pores in Granola‐Type Crystals of Two Different Metal–Organic Frameworks for Enhanced Formaldehyde Removal - Jang, Suin; Jee, Seohyeon; Kim, Raekyung; Lee, Ju Ho; Yoo, Ho Yeon; Park, Woosung; Shin, Jeeyoung; Choi, Kyung Min (Bulletin of the Korean Chemical Society, 2021)
Metal–organic frameworks (MOFs) have introduced heterogeneity in their homogeneous matrix to create new functions that cannot be realized by each MOF individually. In this study, we chemically combined two different MOFs (UiO‐66 and HKUST‐1) in granola‐type granules (termed as HKUST‐1∧UiO‐66) to create a heterojunction of pores in nanocrystalline particles. The structure, morphology, elemental composition, and pore environment were characterized to confirm that two types of pores are in conjunction all over the HKUST‐1∧UiO‐66 granules. We found that the HKUST‐1∧UiO‐66 granules showed an enhanced CO2 sorption capacity than its constituents due to the complexity and the heterojunction of pores inside. Moreover, the HKUST‐1∧UiO‐66 granules present four and two times higher formaldehyde removal capacity than those of the HKUST‐1 and UiO‐66 samples, respectively. The nanocrystalline HKUST‐1 was granulized with UiO‐66 to obtain a heterojunction of pores in granola‐type granules, which enhances capacities for carbon dioxide uptake at low temperature and formaldehyde removal in ambient temperature and pressure.